2018
DOI: 10.1177/0037549718788953
|View full text |Cite
|
Sign up to set email alerts
|

A system dynamics-based model to implement the Theory of Constraints in a healthcare system

Abstract: The management of costly and limited healthcare resources, such as operating rooms, doctors, nurses, and beds, is challenged by the uncertainty of arrivals and the service time of different types of patients. Therefore, healthcare units encounter unbalanced utilization of such resources and unnecessary long patient waiting times. A system dynamics model simulating a typical medium-sized hospital, where different types of patients are served using the same limited resources, is developed to implement the Theory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 43 publications
0
18
0
2
Order By: Relevance
“…It has been reported that more than 75% of instances of delayed discharge were a result of delays in making long-term care arrangements for elderly patients [ 36 , 37 ]. Several studies evaluated the impact of hospital resources on the length of stay [ 35 , 38 , 39 ], while others focused on elderly individuals, chronically ill patients, and their impact on bed occupancy, the average length of stay, and resource consumption [ 40 , 41 ]. The main conflicting results are the impact of changing bed capacity on performance.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that more than 75% of instances of delayed discharge were a result of delays in making long-term care arrangements for elderly patients [ 36 , 37 ]. Several studies evaluated the impact of hospital resources on the length of stay [ 35 , 38 , 39 ], while others focused on elderly individuals, chronically ill patients, and their impact on bed occupancy, the average length of stay, and resource consumption [ 40 , 41 ]. The main conflicting results are the impact of changing bed capacity on performance.…”
Section: Discussionmentioning
confidence: 99%
“…While Vanderby, Carter, Latham and Feindel [18] considers a single specialty at a national level, and provides a tool that helps decision managers planning future workforce, Morgan and Graber-Naidich [19] focused on policies to alleviate the rural care gap in the future. Grida and Zeid [20] proposed a system dynamics model simulating a typical hospital where different types of patients are served using the same limited resources. The model is used to study system capacity, and then to identify bottleneck resources.…”
Section: Empirical Studies Related To This Researchmentioning
confidence: 99%
“…The policy is focused on cooperation between health sectors when serving patients, thereby reducing patient numbers requiring continuous care in health facilities. Grida and Zeid (2019) also applied SD to simulate the hospital system with a scenario that all types of patients were served. However, all hospital systems have limited resources.…”
Section: Introductionmentioning
confidence: 99%